2020
DOI: 10.5194/nhess-2020-60
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Statistical Analysis of Rogue Waves in the Southern North Sea

Abstract: Abstract. A new wave dataset from the southern North Sea covering the period 2011–2016 and composed of wave buoy and radar measurements sampling the sea surface height at frequencies between 1.28–4 Hz was quality controlled and scanned for the presence of rogue waves. Here rogue waves refer to waves whose height exceeds twice the significant wave height. Rogue wave frequencies were analysed, compared to Rayleigh and Forristall distributions, and spatial, seasonal and long-term variability was assessed. Rogue w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…We also see this work as a demonstration how machine learning methods can be helpful in extreme wave research. Some previous studies have attempted to perform binary classification on rogue wave data 44 , 45 (i.e., to predict whether a rogue wave will occur in some block of data or not). We believe that due to the inherently stochastic nature of ocean waves, predicting rogue wave probabilities is a better way forward, and have demonstrated that this can lead to tangible insights.…”
Section: Discussionmentioning
confidence: 99%
“…We also see this work as a demonstration how machine learning methods can be helpful in extreme wave research. Some previous studies have attempted to perform binary classification on rogue wave data 44 , 45 (i.e., to predict whether a rogue wave will occur in some block of data or not). We believe that due to the inherently stochastic nature of ocean waves, predicting rogue wave probabilities is a better way forward, and have demonstrated that this can lead to tangible insights.…”
Section: Discussionmentioning
confidence: 99%